Pneumonia relevant to lung transplantation and pathogen distribution - HE, Xuan; DAI, Hua-ping; CHEN, Qi-rui; MIAO, Jin-bai; SUN, Bing; BAO, Na; HU, Bin; LI, Hui; WU, An-shi; BAN, Cheng-jun; GE, Su-juan; WANG, Chen; et al. (Chinese medical journal, 2013)
Background Pneumonia is the most common cause of morbidity and mortality in lung transplant （LT） recipients. The aim of the present study was to evaluate the incidence, etiology, risk factors and prognosis of pneumonia in LT recipients. Methods The LT cohort consisted of 28 recipients receiving LT in Beijing Chao-Yang Hospital from August 2005 to April 2011. Data collected included demographic data, underlying disorders, time and type of transplant, follow-up information, date of last follow-up, and patient status. A retrospective analysis was made of observational data that were prospectively collected. Results Twenty-two patients of 28 LT recipients had 47 episodes of pneumonia throughout the study period. Thirty- eight episodes of pneumonia in 19 recipients occurred post-LT with a median follow-up of 257.5 days （1-2104 days）, the incidence of pneumonia was 192.4 episodes per 100 LT/year and its median time of onset was 100.5 days （0-946 days） post-transplantation. Bacteria, virus and fungi accounted for 62%, 16% and 15% of the microbial pathogens, respectively. The most frequent were Pseudomonas aeruginosa （20%）, cytomegalovirus （CMV） （15%）, and Aspergillus fumigatus （10%）. A total of 29% （11/38） of pneumonias occurred in the first month post-LT, and then the incidence decreased gradually. The incidence of CMV pneumonia was 25% （7/28） with a median time of 97 days （10-971 days）. More than one bacterial infection and CMV infection were independent risk factors for aspergillus infection. The incidence of pulmonary tuberculosis （TB） was 18% （5/28）, and the history of TB was a risk factor for TB relapse. There were 58% （7/12） of recipients who died of infection, and 71% （5/7） of these died in the first year after LT. Conclusions Pneumonia is still a major cause of morbidity and mortality in LT recipients. The most frequent microorganisms were Pseudornonas aeruginosa, CMV, and Aspergillus fumigates. The incidence of CMV pneumonia decreases with a delayed median time of onset. More than one incidence of bacterial infection and CMV infection are independent risk factors for aspergillus infection. LT recipients are at high risk for TB, and the history of TB is a risk factor for TB relapse.